The dream of a one-stop-shop: meta-analysis on myocardial perfusion CT - Pelgrim, Gert Jan; Henzler, Thomas (European journal of radiology, 2015)
To determine the diagnostic performance of computed tomography (CT) perfusion techniques for the detection of functionally relevant coronary artery disease (CAD) in comparison to reference standards, including invasive coronary angiography (ICA), single photon emission computed tomography (SPECT), and magnetic resonance imaging (MRI). PubMed, Web of Knowledge and Embase were searched from January 1, 1998 until July 1, 2014. The search yielded 9475 articles. After duplicate removal, 6041 were screened on title and abstract. The resulting 276 articles were independently analyzed in full-text by two reviewers, and included if the inclusion criteria were met. The articles reporting diagnostic parameters including true positive, true negative, false positive and false negative were subsequently evaluated for the meta-analysis. Results were pooled according to CT perfusion technique, namely snapshot techniques: single-phase rest, single-phase stress, single-phase dual-energy stress and combined coronary CT angiography [rest] and single-phase stress, as well the dynamic technique: dynamic stress CT perfusion. Twenty-two articles were included in the meta-analysis (1507 subjects). Pooled per-patient sensitivity and specificity of single-phase rest CT compared to rest SPECT were 89% (95% confidence interval [CI], 82-94%) and 88% (95% CI, 78-94%), respectively. Vessel-based sensitivity and specificity of single-phase stress CT compared to ICA-based >70% stenosis were 82% (95% CI, 64-92%) and 78% (95% CI, 61-89%). Segment-based sensitivity and specificity of single-phase dual-energy stress CT in comparison to stress MRI were 75% (95% CI, 60-85%) and 95% (95% CI, 80-99%). Segment-based sensitivity and specificity of dynamic stress CT perfusion compared to stress SPECT were 77% (95% CI, 67-85) and 89% (95% CI, 78-95%). For combined coronary CT angiography and single-phase stress CT, vessel-based sensitivity and specificity in comparison to ICA-based >50% stenosis were 84% (95% CI, 67-93%) and 93% (95% CI, 89-96%). This meta-analysis shows considerable variation in techniques and reference standards for CT of myocardial blood supply. While CT seems sensitive and specific for evaluation of hemodynamically relevant CAD, studies so far are limited in size. Standardization of myocardial perfusion CT technique is essential.